Efficacy of cryoballoon ablation in patients with paroxysmal atrial fibrillation without time to pulmonary vein isolation assessment. (1st December 2018) - Stabile, Giuseppe; Tondo, Claudio; Curnis, Antonio; Lunati, Maurizio; Manfrin, Massimiliano; Molon, Giulio; Sciarra, Luigi; Mantica, Massimo; Iacopino, Saverio; Arena, Giuseppe; Landolina, Maurizio; Arestia, Alberto; et al.
Abstract: Background: Real-time visualization of the electrical activity of the pulmonary veins (PV) is not always possible in the setting of atrial fibrillation (AF) cryoballoon ablation. We investigated the relation between the effective documentation of time to PV isolation and the clinical outcome in a cohort of patients with paroxysmal AF who underwent cryoballoon ablation. Methods: One thousand forty two consecutive patients were enrolled. An inner lumen mapping catheter was typically used to visualize real-time electrical activity inside the PVs. Results: Time to PV isolation was documented in all targeted PVs in 391 patients (Group 1), in 651 patients it was not possible to record PV potentials and assess time to PV isolation in at least one PV (Group 2). In Group 1 a longer procedure duration and ablation time were observed, while a longer fluoroscopy time was observed in Group 2. After a mean follow-up of 14 ± 11 months, 209/1042 (20%) patients had an atrial arrhythmia recurrence (20.2% in Group 1, 19.9% in Group 2, p  = 0.25). Complications occurred in 54/1042 (5.2%) patients without any difference among the two study groups. Conclusion: In our retrospective analysis, in about two thirds of patients undergoing cryoballoon ablation it was not possible to acutely assess time to PV isolation in all PVs. However, one-year freedom from clinically symptomatic atrial tachyarrhythmia was similar to that of patients in which time to PV isolation was documented in all targeted veins. Clinical Trial Registration: clinicaltrials.gov (NCT01007474 ). Highlights: Real-time visualization of the electrical activity of the pulmonary veins is not always possible in the setting of AF cryoablation. In the 63% of patients it was not possible to acutely assess time to pulmonary vein isolation in all targeted pulmonary veins. One-year freedom from atrial tachyarrhythmia was similar to that of patients in which time to PV isolation was documented in all targeted veins.